Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/solr.202000153
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Perovskite Crystal towards Efficient Charge Transport in FASnI3 Perovskite Solar Cells

Abstract: Despite a higher power conversion efficiency (PCE) than other lead‐free perovskite solar cells (PSCs) due to intrinsically excellent optoelectronic properties and suitable bandgaps of tin (Sn) perovskites, Sn‐based PSCs still suffer from issues of stability and efficiency for practical applications. Herein, a novel strategy of tuning perovskite crystal orientation toward ≈45° with respect to the substrate by doping 2,3‐diaminopropionic acid monohydrochloride (2,3‐DAPAC) into formamidinium tin iodide (FASnI3) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 68 publications
0
33
0
Order By: Relevance
“…From Figure a, the main diffraction peaks at 14.1°, 24.8°, 28.0°, 32.3°, and 40.7° that assigned to the crystallographic planes (100), (120), (200), (122), and (222), respectively, confirm that the perovskite possesses the orthorhombic crystal structure and preferred orientation. [ 17,23 ] As C 6 H 7 NO or C 6 H 6 FNO is incorporated, the diffraction peak intensity of the FA 0.75 MA 0.25 SnI 3 perovskite film on the (100) and (200) crystal planes increase significantly, indicative of an obviously enhanced crystallinity. This indicates that the introduction of —OH and —NH 2 groups from C 6 H 7 NO and C 6 H 6 FNO effectively promotes the preferential growth of perovskite crystals along the [100] and [200] crystal directions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From Figure a, the main diffraction peaks at 14.1°, 24.8°, 28.0°, 32.3°, and 40.7° that assigned to the crystallographic planes (100), (120), (200), (122), and (222), respectively, confirm that the perovskite possesses the orthorhombic crystal structure and preferred orientation. [ 17,23 ] As C 6 H 7 NO or C 6 H 6 FNO is incorporated, the diffraction peak intensity of the FA 0.75 MA 0.25 SnI 3 perovskite film on the (100) and (200) crystal planes increase significantly, indicative of an obviously enhanced crystallinity. This indicates that the introduction of —OH and —NH 2 groups from C 6 H 7 NO and C 6 H 6 FNO effectively promotes the preferential growth of perovskite crystals along the [100] and [200] crystal directions.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, we observed that the PL intensity of the perovskite films increases significantly with the doping of C 6 H 7 NO or C 6 H 6 FNO additive (Figure 2c), which is especially obvious for the C 6 H 6 FNO doped film. In view of the fact that the functional groups of —OH and —NH 2 generally form a hydrogen bond with SnI 6 4− octahedron through OH⋯I and NH⋯I, [ 17,23,29 ] the effective passivation of these functional groups to the perovskite induces a significant increase in the PL intensity by reducing the charged traps and suppressing the nonradiative recombination loss assisted by the charged traps.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…proposed a novel molecule of 2,3‐diaminopropionic acid monohydrochloride (2,3‐DAPAC) with both carboxyl and diammonium groups into FASnI 3 . [ 123 ] The results showed that the molecule could not only effectively passivate defects, but also modulate the crystal orientation of perovskite, which made it tilt at 45° relative to the substrate and facilitated charge transport. Consequently, the incorporation of 2,3‐DAPAC into FASnl 3 resulted in dense and smooth perovskite films with less Sn 4+ content (Figure 7h,i).…”
Section: Strategies Of Minimizing Vlossmentioning
confidence: 99%